2000
DOI: 10.1159/000053182
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response to Recombinant Human Growth Hormone (GH) in Children with Idiopathic Growth Retardation by Level of Maximum GH Peak during GH Stimulation Tests

Abstract: Due to their lack of reproducibility, it is unlikely that GH stimulation tests can provide reliable diagnostic information to distinguish partial isolated GH deficiency (GHD) from idiopathic short stature (ISS). We hypothesized that the classical distinction between these groups, essentially based on stimulatory GH peaks, is artificial and that, as a consequence, the average response to GH treatment will not be different between them. The hypothesized lack of prognostic validity of stimulatory GH peaks was stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Other investigators have also reported that peak GH values obtained during GHST are poor predictors of subsequent growth for all but the lowest peak GH values [13,14]. Interestingly, Wyatt et al [15] noted in 1995 that while 80% of the pediatric endocrinologists who responded to their questionnaire used two GH stimulation tests, only 32% believe the results of such tests predicted a response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have also reported that peak GH values obtained during GHST are poor predictors of subsequent growth for all but the lowest peak GH values [13,14]. Interestingly, Wyatt et al [15] noted in 1995 that while 80% of the pediatric endocrinologists who responded to their questionnaire used two GH stimulation tests, only 32% believe the results of such tests predicted a response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of GHD was more pronounced in our subjects which is shown by a significantly lower mean GH peak after the provocation test. In other words, in the original group patients with less severe GHD were included, and it is well known that these patients will respond less favorable to GH treatment [13]. In addition, our group was composed from only 2 university centers applying rather stringent criteria for the diagnosis and laboratory methods which may help to reduce the variability arising from data composition from a large number of centers.…”
Section: Discussionmentioning
confidence: 99%
“…Van den Broeck et al [39] reviewed the Dutch Growth Hormone Register and analyzed whether longterm response to therapy of 435 children could be predicted by peak GH response at the time of diagnosis. Children were diagnosed as severe GHD, partial GHD, or ISS based on GH response to GH stimulation tests (<10 mU/L or 5 ng/mL, 10-20 mU/L or 5-10 ng/mL, >20 mU/L or 10 ng/mL, respectively).…”
Section: Do Gh Stimulation Tests Predict Response To Gh Therapy?mentioning
confidence: 99%
“…The response to therapy was significantly better in children with severe GHD, but was not statistically different between children with partial GHD and those with ISS. The authors conclude that ''there is a lack of prognostic validity of GH stimulation tests as they are currently applied'' [39].…”
Section: Do Gh Stimulation Tests Predict Response To Gh Therapy?mentioning
confidence: 99%